Dinâmica da paisagem costeira da Coroa do Meio e Atalaia - Aracaju-SE - Santos, Geisedrielly Castro dos (2012)
The aim of this study is to understand the coastal landscape dynamics of the Coroa do Meio e Atalaia in Aracaju-SE. The methodological approach used was: literature review; landscape units and shoreline mapping for a range of different time (1955, 1965, 1978, 1984, 2003 e 2008); shoreline monitoring using beach profiles done between 2008 and 2010; work field and Gis-based environmental data integration. The following landscape units were identified: Beach, Dune/Interdune, Fluviomarine Terrace, Tidal Plain and Human Occupation. The results showed that the landscape changes were primarily due to the expansion of the Human Occupancy, which contributed to the reduction of other landscape units. The remaining units in 2008 were: Tidal Plain, Beach and Human Occupation. The shoreline analysis showed that between 1955 and 2008 progradation occurred at the Atalaia beach and high variability occurred at Artistas beach. The Atalaia beach progradation has been identified since 1984, after stabilization of the right bank of the Sergipe river mouth. The great shoreline variability was not directly influenced by the occupation expansion area; before occupation, shoreline retreat episodes have been recorded. However, the occupation expansion area contributed to make evident the erosion episodes at the Artistas beach. In the short-term analysis of the Artistas beach, the sediment budget was positive between 2008 and 2009 and negative between 2009 to 2010. This analysis confirms the great variability of the shoreline due to the Sergipe river mouth dynamics. Finally, this study concluded that human occupation was the predominant landscape modeller agent, assuming two behaviors: i transformant agent: its expansion contributed to the decrease of the Dune / Interdune, Tidal Plain and Fluviomarine Terrace unit areas and, ii - transformant agent that suffer with its actions: shoreline progradation favored the occupation expansion over the accretional area and the shoreline retreat caused economic losses. Thus, this study provides subsidies for environmental planning of the study area.